2016
DOI: 10.3390/ijerph13040366
|View full text |Cite
|
Sign up to set email alerts
|

Association between Atmospheric Fine Particulate Matter and Hospital Admissions for Chronic Obstructive Pulmonary Disease in Southwestern Taiwan: A Population-Based Study

Abstract: Objectives: This paper reports on the findings of a population-based study to evaluate the relationship between atmospheric fine particulate matter (PM2.5) levels and hospital admissions for chronic obstructive pulmonary disease (COPD) in southwestern Taiwan over a three-year period, 2008–2010. Methods: Data on hospital admissions for COPD and PM2.5 levels were obtained from the National Health Insurance Research database (NHIRD) and the Environmental Protection Administration from 2008 to 2010, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 31 publications
1
18
1
Order By: Relevance
“…Currently, it is a well‐known air pollutant threatening public health. Clinical studies reported that long‐term exposure to the particles associated with reduction in pulmonary function, exacerbation of chronic respiratory diseases such as asthma and chronic obstructive pulmonary disease (COPD), and increased incidence and mortality of lung cancer . Epidemiological studies revealed an inverse relationship between the particles inhalation and human average life span .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, it is a well‐known air pollutant threatening public health. Clinical studies reported that long‐term exposure to the particles associated with reduction in pulmonary function, exacerbation of chronic respiratory diseases such as asthma and chronic obstructive pulmonary disease (COPD), and increased incidence and mortality of lung cancer . Epidemiological studies revealed an inverse relationship between the particles inhalation and human average life span .…”
Section: Introductionmentioning
confidence: 99%
“…The PM 2.5 concentration in Beijing during 2013 significantly exceeded the health standard suggested by the World Health Organization (WHO) [ 2 , 3 , 4 ], and has caused the total economic losses of 246.26 billion Yuan (approximately 1.1% of the national GDP) during 2007 [ 5 ]. Not only that, the serious air pollution in China caused significant public health impacts [ 6 , 7 ]. The Global Burden of Disease (GBD) study undertaken by Institute for Health Metrics and Evaluation and World Health Organization (WHO) linked over 3.2 million premature deaths to PM pollution in 2010, and roughly one-third (1.23 million) of the world’s estimated PM pollution-related premature deaths were in China [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, fine particulate matter (PM 2.5 ), a type of pollutant, has been verified to be unhealthy for humans and the living environment, as it can cause lung cancer, respiratory and cardiovascular diseases, affect transportation, as well as increase mortality [1,2,3,4]. Recently, PM 2.5 pollution has become the greatest environmental problem in China and is therefore attracting growing public concern.…”
Section: Introductionmentioning
confidence: 99%